HIV vaccines. - Mcmichael, A (2006)
A prophylactic vaccine for HIV-1 is badly needed. Despite 20 years of effort, it is still a long way off. However, considerable progress has been made in understanding the problem. The virus envelope has evolved to evade neutralizing antibodies in an extraordinary way, yet a vaccine that can stimulate such antibodies remains the best hope. Anti-HIV-1 T cell responses are evaded by continuous mutation of the virus. Vaccine strategies that concentrate on stimulating T cell immunity will at best generate broadly reactive and persisting T cell responses that can suppress virus without preventing infection, limiting or preventing the damage the virus causes. The SIV macaque models give encouragement that this is possible, but they need further understanding. Therapeutic vaccination should also be considered.